Debiasing halo effect: auditor reputation and the role of auditing learning on financial statements user trust - Rama, Radian Sri; T, Sutrisno; Saraswati, Erwin; Rahman, Aulia Fuad (International research journal of management, IT and social sciences, 2020)
The purpose of this study was to examine the effect of auditor reputation (big four and non-big four) and auditing learning (with audit learning and without audit learning) on the trust of users of financial statements. Testing the influence of the auditor’s reputation and learning will show a halo effect on users of financial statements. The research method used was an experiment. Participants were 102 students. Data analysis was performed with the two-way Anova test. The results showed a halo effect so that the auditor’s reputation and audit learning affected the users of financial statements.